Dynamic modelling and adaptive PID control of palm oil biodiesel engine - Azuwir Mohd Nor (School of Manufacturing Engineering, 2013)
This study is aimed at the development of mathematical models and adaptive controller of automotive engine fuelled with palm oil methyl esters (palm oil biodiesel).